2014
DOI: 10.1111/1440-1681.12213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of opioid (tramadol) treatment on testicular functions in adult male rats: The role of nitric oxide and oxidative stress

Abstract: Nowadays, tramadol hydrochloride is frequently used as a pain reliever, and for the treatment of premature ejaculation. Decreased semen quality was noted in chronic tramadol users. The present study aimed to elucidate the effects of tramadol on the testicular functions of adult male rats. A total of 40 albino adult male rats were divided into control and tramadol groups, with 20 rats for each group. Rats of the tramadol group were subcutaneously injected with 40 mg/kg three times per week for 8 weeks. The cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 33 publications
16
41
1
Order By: Relevance
“…The concentration of serum total cholesterol determines in part, the concentration of steroid hormones in serum. Consistent with this present study, previous reports had demonstrated that tramadol reduced serum concentration of total cholesterol (Abdellatief et al, 2014;Ahmed and Kurkar, 2014). The consequence of this is that steroid hormones concentration will likely be raised in tadalafil treated group and lowered in tramadol and sildenafil+tramadol treated groups, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The concentration of serum total cholesterol determines in part, the concentration of steroid hormones in serum. Consistent with this present study, previous reports had demonstrated that tramadol reduced serum concentration of total cholesterol (Abdellatief et al, 2014;Ahmed and Kurkar, 2014). The consequence of this is that steroid hormones concentration will likely be raised in tadalafil treated group and lowered in tramadol and sildenafil+tramadol treated groups, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Apart from atherogenic benefits offered by recreational use of tramadol and sildenafil+tramadol, results of this present study further suggest that, serum levels of testosterone in tramadol and sildenafil+tramadol treated groups may be negatively affected, considering the decreased serum total cholesterol in these groups. Reduced serum concentration of testosterone (a steroid hormone) following tramadol administration, has been previously reported (Abdellatief et al, 2014;Ahmed and Kurkar, 2014). This effect may be attributed to the depletion of serum total cholesterol (substrate for testosterone synthesis) by tramadol.…”
Section: Discussionmentioning
confidence: 85%
“…27 Similarly, dilated cortical vessels with RBCs extravasation and congestion of submeningeal vessels were previously documented following long term intake of tramadol. [23][24][25][26][27][28] High oxygen consumption, increased polyunsaturated fatty acids, and low antioxidants level render the brain tissue highly susceptible to oxidative stress. 29 MDA is the most abundant metabolite of free radical-induced lipid peroxidation cascade in biological systems and is commonly used as a marker for oxidative stress.…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, it is a good time for both partners to stop if they are smokers. There are many studies on the deleterious effects of recreational drugs, sports drugs (anabolic steroids), marijuana, opioids and tramadol on spermatogenesis in men, and folliculogenesis in women [17][18][19][20].…”
Section: Prerequisitesmentioning
confidence: 99%